Critical success factors for business intelligence system implementation in public sector organisation. (2017) - Nasab, Samaneh Salehi; Jaryani, Farhang; Selamat, Harihodin Bin; Masrom, Maslin
Business intelligence (BI) system offers competitive advantages to public organisations by gathering, storing and analysing large volume of data for effective decision making. Although, the rate of BI implementation within public sector organisations is increasing, still some of the BI implementation projects fail. Hence, this study aims to investigate the critical success factors (CSFs), which affect the success of BI system implementation in public sector organisations. This study structures previous research by presenting a comprehensive classification of CSFs in the area of BI system implementation success. The review of the literature identifies the large number of CSFs for BI success mostly related to private sector organisations. Moreover, prior studies indicate that there has not been enough research on impact of culture on success of BI system implementation. Finally, the main finding of this study revealed achieving success in BI system implementation in public sector organisation is associated with four factors namely culture of learning, decision-making culture, information sharing culture and collaboration culture under culture dimension.